The Relationship Between a History of Chronic Energy Deficiency and the Incidence of Stunting in Toddlers Aged 24-59 Months - Erin Desweni; Hafiza Fil Ihsan; Putri Engla Pasalina (Griya Eka Sejahtera, 2026)
Background: The prevalence of stunting in Indonesia is 43% among children aged 24-59 months and 41.2% among children aged 12-23 months. The prevalence of stunting in toddlers in West Sumatra in 2020 was 25.6%. The prevalence of stunting in toddlers in Padang City in 2021 was 22.6%. Stunting carries the risk of reduced intellectual potential and impaired growth. The purpose of this study was to determine the relationship between a history of anemia during pregnancy, chronic energy deficiency, and pre-pregnancy body mass index (BMI) with the incidence of stunting in toddlers aged 24-59 months in Balai Gadang Village, within the Air Dingin Community Health Center (Puskesmas) working area of ​​Padang City in 2022.Methods: The type and design of this study were descriptive analytical with a case-control design. This study was conducted in the Air Dingin Community Health Center working area of ​​Padang City from January to March 2022. The population was 1,356 people and the sample size was 25. Sampling was carried out using a consecutive sampling technique. Data analysis was performed bivariately using the chi-square test.Results: The results of this study indicate a relationship between a history of anemia and the incidence of stunting (p=0.000), a history of Chronic Energy Deficiency (p=0.000), and a history of pre-pregnancy body mass index (BMI) and the incidence of stunting (p=0.000).Conclusion: The conclusion of this study is that there is a relationship between a history of anemia during pregnancy, Chronic Energy Deficiency, and pre-pregnancy BMI with the incidence of stunting